FACTORS AFFECTING CREDIT ACCESSIBILITY IN THE BANK OF AGRICULTURE, KATSINA STATE IN NIGERIA - Muhammad, Ahmad; Abdulmumini, Lawan; Ubandoma, G. A. (FUDMA JOURNAL OF SCIENCES, 2025)
The study analyzes the factors affecting credit accessibility in the Bank of Agriculture Funtua Katsina State of Nigeria. A multi-stage sampling technique was used to draw data from 176 respondents in the study area using structured questionnaire, also secondary data was collected from the Bank of Agriculture, Funtua in Katsina State. Data collected was analyzed using descriptive statistics and multiple linear regression. The study revealed that 55% of the respondents were in their youthful ages, also 49% had no formal education, The regression coefficient of age of farmer and household size were significant at 5% probability level but age of farmer is inversely related, access to farm inputs,  access to extension information and farmer’s other business were significant at 1% probability level, interest rate subsidies was found to be significant at 10% probability level and limited bank branches, lack of information about the bank and lack of collateral were the problems faced by the respondents in loan acquisition, the study therefore recommends establishment of more bank branches and more efficient extension service on the importance of credits as the solutions to the said problem.
Keywords: Credit; Farmers; Bank of Agriculture